1986
DOI: 10.1128/iai.54.1.43-49.1986
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a uroepithelial cell adhesin from a uropathogenic isolate of Proteus mirabilis

Abstract: Proteus mirabilis is a frequent cause of urinary tract infections in rehabilitation hospitals and among persons with structural abnormalities of the urinary tract. Adherence to uroepithelial tissues may be an important virulence determinant in these infections because most Proteus strains adhere to desquamated uroepithelial cells. To identify the adherence factor responsible for this phenomenon, we sheared outer membrane material from 35S04-radiolabeled bacteria and allowed it to bind to uroepithelial cells. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 25 publications
3
83
0
Order By: Relevance
“…Fimbriae and adhesins of P. mirabilis UCA/NAF Wray et al (1986) isolated and identified UCA from an isolate of uropathogenic P. mirabilis. This fimbria was found to be organized as long and flexible rods, with a thin filament of 4 nm predominating.…”
Section: Bacterial Adhesion To Uroepithelial Tractmentioning
confidence: 99%
“…Fimbriae and adhesins of P. mirabilis UCA/NAF Wray et al (1986) isolated and identified UCA from an isolate of uropathogenic P. mirabilis. This fimbria was found to be organized as long and flexible rods, with a thin filament of 4 nm predominating.…”
Section: Bacterial Adhesion To Uroepithelial Tractmentioning
confidence: 99%
“…These swarmer cells also exhibit reduced expression of fimbriae (Mobley et al, 1996;Jansen et al, 2003), suggesting possible co-ordinate expression between flagella and fimbriae. Prior to the sequencing of the P. mirabilis genome, expression of five different fimbriae had been documented in P. mirabilis: MR/P fimbriae (Adegbola et al, 1983;Bahrani et al, 1994), uroepithelial cell adhesin (UCA, also known as non-agglutinating fimbriae or NAF) (Wray et al, 1986;Cook et al, 1995), P. mirabilis fimbriae (PMF) (Adegbola et al, 1983;Massad et al, 1994a), ambient temperature fimbriae (ATF) (Massad et al, 1994b) and P. mirabilis P-like pili (PMP) (Bijlsma et al, 1995). The MR/P fimbria is encoded by an operon containing nine genes (Bahrani et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Uroepithelial cell adhesin was the first fimbriae identified in P. mirabilis (Wray et al, 1986). In this pioneer study, the authors proved the adhesive properties of the isolated fimbrial material.…”
mentioning
confidence: 97%
“…Adherence to human uroepithelial cells was assessed according to the procedure described by Wray et al (1986). Pellets containing 2 9 10 5 uroepithelial cells, recovered after centrifugation of urine form three healthy female donors, were suspended in 1 mL of BSG containing 5 9 10 7 Pr 2921 and UM1 bacteria and incubated for 1 h at 37°C.…”
mentioning
confidence: 99%